Abuse of Islamic Law and Child Marriage in South-Sulawesi Indonesia - Salenda, Kasjim (Al-Jamiah: Journal of Islamic Studies, 2016)
This article examines the prevalence of child marriage in South-Sulawesi Indonesia including peopleâs perceptions and its factors contributing to child marriage and the use religion to justify their actions. They perceive child marriage as the marriage conducted prior to the age of 16 for woman and of 19 for man as stipulated in the Marriage Law No.1 of 1974, as well as the marriage before âakil baligâ. Various determinants for child marriage are cultural norms or values of âsiriâ (shame) for family honour; family prestige and kinship; uneducated parents; economic burden for family and inconsistency in legislation. No religious teachings or Islamic Law clearly support the prevalence of child marriage because the purpose of marriage in Islam is to perform a happy and harmonious relationship among the couple. The use of the Prophet Muhammadâs marriage to Aisha in the age of six as the fundamental basis for child marriage is unjustified.[Tulisan ini membahas kasus-kasus pernikahan anak di Sulawesi Selatan, termasuk persepsi masyarakat dan faktor-faktor pendukungnya diantaranya penggunaan dalil agama (Islam) untuk membenarkan tindakan tersebut. Masyarakat memahami pernikahan anak sebagaimana tercantum dalam UU Pernikahan No. 1 Tahun 1974 bahwa pernikahan anak terjadi pada usia dibawah 19 tahun bagi laki-laki dan 16 tahun bagi perempuan dan atau mereka yang belum akil baligâ. Beberapa factor dominan dalam pernikahan anak antara lain; norma adat lokal (âsiri), kehormatan keluarga dan kerabat, orangtua yang kurang terpelajar, beban ekonomi keluarga dan ketidakkonsisten penegakan peraturan. Pada dasarnya tidak ada ajaran Islam atau fiqih yang secara tegas mendukung pernikahan anak karena tujuan dari pernikahan dalam Islam adalah kebahagiaan dan keharmonisan hubungan antar suami istri. Menggunakan rujukan pernikahan Nabi Muhammad dengan Aisyah saat usia enam tahun merupakan perkara yang tidak bisa dibenarkan.]